"The World is too much with us:" The Character of Literary Studies Today - Zekiye Antakyalıoğlu (Ideas: Journal of English Literary Studies)
Literary studies in the new millennium are described as “post-theoretical,” which implies a paradigm shift from the deconstructive linchpin of capital-t Theory, to a more socially, politically and environmentally engaged, future-oriented, and reparative drive in our discipline. There is a change of attention from the relativist epistemology of poststructuralism to realist ontology in the new fields of study such as posthumanism and new materialism. Post-theory holds two concurrent attitudes toward Theory: acknowledgement and critique. On the one hand, it is indebted to the legacy of Theory and forms discursive practices in relation to it; on the other hand, it is critical of Theory’s antiessentialism or lack of ethos, and reassesses its foundational axioms with contemporary ontological anxieties and motives. Ours is a chaotic century with manifold problems such as terrorism, war, economic crisis, COVID-19 pandemic, climate changes, oil and water crises, Anthropocene, consumerism, migration, digitalisation, and the question of democracy, etc. This sense of emergency, and its representations in literature, eventually, calls for “character” (essential, mental and moral vision, ethos) and genuine critique (evaluation) from the academics in humanities. This paper aims to offer an outline of the network of practices in literary studies as well as their ethical and aesthetic allegiances with this demand for “character” in mind.